The Impact of Accounting Science and Entrepreneurship Literacy on Students' Entrepreneurship Motivation - Januardi, Januardi; Lestari, Neta Dian; Valianti, Reva Maria (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The student already has a strong grasp of business literacy, and he naturally has access to information on how businesses are organized. When participating in practice sessions or seminars on entrepreneurship that are organized by various organizations, women with strong leadership motivation comes from their level of activity. The current study employs a quantitative approach with the goal of determining the most significant impact of the Entrepreneurial Literacy and Accounting Science on the motivation of entrepreneurial students. A straightforward, effective method that is used is the sampling and responding technique. using a sample size of approximately 100 respondents with a 5% error rate. This study employed the Multiple Linear Regression Analysis method. The results of the study indicate that Entrepreneurship Literacy and Accounting Science are relevant to 2020 Student Motivation for Entrepreneurs in both partial (t) and simultaneous (F) forms.